Consensus on melanonychia nail plate dermoscopy Consenso sobre dermatoscopia da placa ungueal em melanoniquias - Nilton Di Chiacchio; Débora Cadore de Farias; Bianca Maria Piraccini; Sergio Henrique Hirata; Bertrand Richert; Martin Zaiac; Ralph Daniel; Pier Alessandro Fanti; Josette Andre; Beth S Ruben; Philip Fleckman; Phoebe Rich; et al. (Sociedade Brasileira de Dermatologia, 2013)
This statement, focused on melanonychia and nail plate dermoscopy, is intended to guide medical professionals working with melanonychia and to assist choosing appropriate management for melanonychia patients. The International Study Group on Melanonychia was founded in 2007 and currently has 30 members, including nail experts and dermatopathologists with special expertise in nails. The need for common definitions of nail plate dermoscopy was addressed during the Second Meeting of this Group held in February 2008. Prior to this meeting and to date (2010) there have been no evidence-based guidelines on the use of dermoscopy in the management of nail pigmentation. Este consenso, com foco em melanoníquia e dermatoscopia da lâmina ungueal, se destina a orientar os médicos que trabalham com melanoníquia e auxiliar no manejo destes pacientes. O grupo internacional de estudos sobre melanoníquia foi fundada em 2007 e tem agora 30 membros, incluindo dermatologistas e dermatopatologistas com conhecimento especializado em unhas. A necessidade de definições comuns de dermatoscopia da lâmina ungueal foi abordada durante a segunda reunião deste grupo, realizada em fevereiro de 2008. Antes desta reunião e até a presente, não existem orientações com base em evidências sobre a utilização de dermatoscopia da placa ungueal.